2016
DOI: 10.1021/acs.iecr.6b03729
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer of CO2 in a Carbonated Water–Oil System at High Pressures

Abstract: In this paper, CO2 diffusion coefficients in a carbonate water–oil system are determined by measuring the pressure buildup in the closed water–oil system experimentally and modeling the pressure change mathematically. The mathematical method of investigating one-dimensional, time-dependent heat conduction in a composite medium is adopted to solve the mass transfer problem between two liquid phases. The model is combined with well-designed trial-and-error method to determine diffusion coefficients of CO2 in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…The diffusivity of the gas was found to increase with temperature and pressure (Jamialahmadi et al, 2006). Shu et al (2017) concluded that the pressure is the most important factor affecting the mass transfer during the gas injection. They pointed that the interface concentration of CO 2 in the oil phase increased with the pressure.…”
Section: Model Verificationmentioning
confidence: 99%
“…The diffusivity of the gas was found to increase with temperature and pressure (Jamialahmadi et al, 2006). Shu et al (2017) concluded that the pressure is the most important factor affecting the mass transfer during the gas injection. They pointed that the interface concentration of CO 2 in the oil phase increased with the pressure.…”
Section: Model Verificationmentioning
confidence: 99%
“…Due to the gradual and steady nature of the CO 2 transfer, the swelling and expansion of oil are expected to happen steadily. Hence in porous media flooded by CW, oil ganglia are believed to expand continuously leading to high overall swelling . Moreover, as water loses the dissolved CO 2 , slight decreases ensue in both the density and the viscosity of the aqueous phase …”
Section: Introductionmentioning
confidence: 99%
“…Hence in porous media flooded by CW, oil ganglia are believed to expand continuously leading to high overall swelling. 10,11 Moreover, as water loses the dissolved CO 2 , slight decreases ensue in both the density and the viscosity of the aqueous phase. [12][13][14] The theory is that the incremental oil recovery is obtained due to the mass transfer of CO 2 from the water phase into the oil phase, causing oil mobilization because of oil swelling and coalescence of the isolated oil ganglia, viscosity reduction, 6,15-18 and a reduced oil-water IFT.…”
Section: Introductionmentioning
confidence: 99%
“…When the system reaches equilibrium, even if the solubility of CO 2 in the oleic phase is not saturated (CO 2 concentration is far from saturated solubility), the CO 2 in the aqueous phase will not continue to move to the oleic phase. The CO 2 distribution between the aqueous and oleic phases according to a certain partition coefficient (k pc ) [11], which reflects the diffusion degree of CO 2 to the oleic phase, is presented in Table 1. The calculation results are in good agreement with the previous experiments [11,38,39].…”
Section: Diffusion Process and Distribution Of Comentioning
confidence: 99%
“…Unlike other methods, CWI technology uses saturated CO 2 water to displace formed crude oil, which has the advantages of gas injection and water injection (WI). CWI is less affected by reservoir heterogeneity, which leads to a higher sweep efficiency [10,11], and it significantly reduces the residual oil saturation and improves the oil recovery [12]. In addition, the traditional CO 2 injection and WAG require continuous injection for a large amount of CO 2 , which leads to the economic decline of many reservoir projects.…”
Section: Introductionmentioning
confidence: 99%